Treatment effects of adjunct group music therapy in inpatients with chronic schizophrenia: a systematic review - Lam, Lissa; Chang, Wing Chung; Grimmer, Karen (Frontiers in Psychiatry, 2023)
Introduction Pharmacological treatment may be effective for treating positive symptoms of schizophrenia; no evidence of clinically significant effects on negative and cognitive symptoms, social and behavioral functioning. This review investigated treatment outcomes of multiple (at least four sessions in 4 weeks) group music therapy sessions adjunct to standard care in inpatients with chronic schizophrenia. Methods A systematic review search of five electronic medical and psychological databases conducted using keywords “music therapy” and “schizophrenia” up to December 2021. Screening was performed for published articles on any adjunct multiple group music therapy (four sessions in 4 weeks minimum) adjunct to “treatment as usual” for inpatients with “chronic” schizophrenia. All study outcomes were all included. Risk of bias of all studies was assessed. Results 1160 articles were screened, and 13 randomized controlled trials (RCTs) with a total of 1,114 inpatients were included. Ten RCTs reported open group sessions with active structured music making (ASMM) combining passive music listening (PML) and/or active singing, playing instruments, and improvisations while three other studies applied PML only. Four studies reported significant outcomes for both positive and negative symptoms. Ten of the thirteen studies recorded significant improvements in negative symptoms, behavioral and social functioning. Lasting significant effects were found in a longitudinal RCT with 272 samples evaluated unguided pre-recorded PML as a coping method lasting up to six months and similar results found in another two longitudinal RCTs. Secondary outcomes measured cognition, mood, social interest and function, self-care ability, interpersonal relationships, and QoL all showed significant outcomes. The significance level for pre-post intervention and between-group measures ranged from p < 0.001 to p < 0.05. No negative effects were reported in any studies. Conclusion Evidence from this review suggests rehabilitation with adjunctive regular PML or combined ASMM in group settings may provide therapeutic engagement, contributing to improvements in social interest and participation. PML is low-cost and non-invasive therapy. Enhancing overall QoL as one type of psychosocial therapy. More rigorous longitudinal studies with larger sample sizes are needed to investigate whether regular long-term individual PML and active group music therapy have the same significant treatment effects as coping and rehabilitation strategies.